NL ARMS Netherlands Annual Review of Military Studies 2018 Coastal Border Control: From Data and Tasks to Deployment and Law Enforcement (NL ARMS, Netherlands Annual Review of Military Studies, 2018)
This book provides a comprehensive study of border control: from data analysis and information warfare, frameworks for command and control, and game-theoretic risk management, up to the (optimal) deployment of law enforcement missions. Innovative about this book is that it approaches the subject from several angles, aiming to connect theory and practice of law enforcement missions with risk management and/ or quantitative modelling. Some chapters focus on legal challenges and information warfare, while others provide quantitative modelling of military asset deployment in the area of interest, or show the benefits of cooperative wireless sensor networks for border control. A case study of the Dutch Border Security Team supplements the theory. The publication is ideally suited for reference use by students, academicians, researchers and professionals in the field of border control and related areas. H. Monsuur is Professor of Military Operations Research, J.M. Jansen is Associate Professor of Operational ICT, and F.J. Marchal is Lecturer of International/Military Law at the Faculty of Military Sciences of the Netherlands Defence Academy in Den Helder, The Netherlands.